An observational study on causes of female infertility - Thatipelli, Ravi Chander; Parunandi, Yashaswini; Nousheen, Syed; Shenkeshi, Suvarchala; Fathima, Hijazi; Anitha, Adaboina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Infertility is characterized by the inability to conceive after 12 months or more of consistent, unprotected sexual activity. It can be caused by a variety of abnormalities of the female reproductive system. The aim is to study the causes of female infertility. The main objective is to identify the common causes and risk factors causing infertility in females. Methods: The study population consisted of 383 infertile women. The study was conducted at Laxmi Narasimha hospital, Hanamkonda, in Warangal region for a period of 6 months. The tool used for the study was specifically designed questionnaire, which included the demographic data, and questions concerning the causes of infertility. Results: Through our study it is observed that polycystic ovarian disease (PCOD), hypothyroidism, ovarian cyst, tubal damage, uterine abnormality, uterine fibroids, endometriosis are the causes of female infertility. The highest prevalence of infertility was found in patients with PCOD (30.5%), followed by patients with PCOD with other conditions (24%) (mostly PCOD with hypothyroidism). Highest prevalence of infertility in females was observed in the age group between 21-30 years. It is noticed that some patients were with infertility for unknown cause (16%). Conclusions: In our study, we concluded that the PCOD is the major cause in both primary and secondary infertility in females. Higher prevalence of infertility was seen in age group of 21-30 years. Certain patients were having unexplained infertility. Infertility is now a widespread problem, and understanding the causes is the first step toward resolving it.